2014
DOI: 10.1017/jfm.2014.201
|View full text |Cite
|
Sign up to set email alerts
|

Drops and bubbles in wedges

Abstract: We investigate experimentally the spontaneous motion of drops and bubbles confined between two plates forming a narrow wedge. Such discoidal objects migrate under the gradient in interfacial energy induced by the non-homogeneous confinement. The resulting capillary driving force is balanced by viscous resistance. The viscous friction on a drop bridging parallel plates is estimated by measuring its sliding velocity under gravity. The viscous forces are the sum of two contributions, from the bulk of the liquid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 43 publications
4
68
0
Order By: Relevance
“…This prediction is, in particular, important in the dynamics of foams sliding against a wall (Cantat 2013). It also enables one to account for the motion of a drop bridging the walls of a Hele-Shaw cell and flowing under its own weight (Reyssat 2014). Equivalently, Park & Homsy (1984) have shown that in the case of a non-wetting fluid displacing a wetting phase in a Hele-Shaw cell, dynamic wetting modifies the interfacial pressure jump by adding a term of order (γ /h)Ca 2/3 w .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This prediction is, in particular, important in the dynamics of foams sliding against a wall (Cantat 2013). It also enables one to account for the motion of a drop bridging the walls of a Hele-Shaw cell and flowing under its own weight (Reyssat 2014). Equivalently, Park & Homsy (1984) have shown that in the case of a non-wetting fluid displacing a wetting phase in a Hele-Shaw cell, dynamic wetting modifies the interfacial pressure jump by adding a term of order (γ /h)Ca 2/3 w .…”
Section: Discussionmentioning
confidence: 96%
“…Conversely, Lorenceau & Quéré (2004) showed that a drop of wetting oil deposited on a conical fibre spontaneously moves away from the tip. More recently, gradients of confinement have been proposed as a solution to propel droplets in narrow channels (Renvoisé et al 2009) or as an elegant tool to produce and guide droplets in microfluidic devices (Dangla, Kayi & Baroud 2013), while Reyssat (2014) analysed the dynamics of drops and bubbles confined in wedges.…”
Section: Introductionmentioning
confidence: 99%
“…145,146,147 This principle is based on capillary pressure gradients that evolve when bubbles are deformed by a tapered channel. 148 Another effective geometrical approach involves the use of hemispherical channels and wells which can capture traveling bubbles in a highly gas permeable microchannel (e.g., Poly-dimethyl siloxane, PDMS, channels), such that the bubbles trapped spontaneously dissipate. 149 This approach is limited by the permeability of the gas in the channel material and is effective when the gas evolution rate is slow.…”
Section: Geometrical Approachesmentioning
confidence: 99%
“…The experimental data are plotted against the theoretical equation ( that for low Ca ranges, the dissipation in the thin film (Keiser et al 2018) and in the dynamic meniscus (Reyssat 2014) have to be taken into account.…”
Section: Experimental Results For Drop Velocitymentioning
confidence: 99%